Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1200/jco.2002.20.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Long-Term Survivors of Testicular Cancer: A Population-Based Case-Control Study

Abstract: French long-term survivors of testicular cancer do not express more impairment of health-related quality of life or familial or professional life in comparison with healthy men. They did have more sexual life problems and found difficulty in borrowing from banks. This information should be used by practitioners to help their patients cope with their disease and return to normal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 46 publications
3
82
1
5
Order By: Relevance
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have in fact suggested that men are less able to undertake a caregiving role and assume the burdens of home and family maintenance compared with women. [3][4][5][6][7][8][9][10][11] Thus, a woman becomes willing sooner in the marriage to commit to the burdens of having a sick spouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some describe the influence on health-related QL (Fossa et al, 1999;Joly et al, 2002). Others show the necessarity of an open dialogue between doctors and patients on sexual difficulties (Bourgeois-Law and Lotocki, 1999;Hawighorst-Knapstein et al, 2002).…”
mentioning
confidence: 99%
“…Furthermore, there is a lack of research into the QoL of the growing group of long-term TCSs. Currently, there are only a few studies that did include long-term survivors [1,6,13,18], whereas at this point in time, approximately 25 years after the medical breakthrough in treatment, the group of long-term survivors has grown large enough to provide adequate statistical power to examine their QoL. Then again, the inclusion of long-term survivors does confront researchers with specific methodological concerns.…”
Section: Introductionmentioning
confidence: 99%